The Portapotty Experiment: Neoliberal approaches to the intertwined epidemics of opioid-related overdose and HIV/HCV, and why we need cultural anthropologists in the South Bronx - Wolfson-Stofko, Brett (Dialect Anthropol, 2016)
The following report from the field focuses on the authors’ collective efforts to operate an ad hoc safer injection facility (SIF) out of portapotties (portable toilets) in an area of the South Bronx that has consistently experienced some of the highest overdose morbidity and mortality rates in New York City over the past decade (New York City Department of Health and Mental Hygiene, 2011, 2015, 2016). Safer injection facilities (also known as supervised injection facilities, drug consumption rooms, etc.) operating outside the US provide a legal, hygienic, and supervised environment for individuals to use drugs in order to minimize the likelihood of fatal overdose and the spread of blood-borne infections while reducing public injection. In the US, the operation of SIFs is federally prohibited by the federal “Crack House” statute though federal, state, and local elected officials can sanction their operation to various degrees (Beletsky, Davis, Anderson, & Burris, 2008). The activists, researchers, undergraduate students and peers from syringe exchange programs who came together to operate the portapotties discovered that they were, in many ways, emblematic of neoliberal solutions to disease prevention: primarily focused on auditing individual risk behaviors and virtually blind to the wider social context that shapes those lives. That social context — the culture of drug injection — was and is out in the open for all of us to see. Going forward, the cultural anthropologist’s toolbox will be opened up and used by large groups of undergraduate students to better understand the culture of drug use and how it is changing.